Habilidades sociais e desempenho acadêmico : processos cognitivos como moderadores e mediadores - Feitosa, Fabio Biasotto (2007)
The general goal of this work was to examine the role of analogous mechanisms of information processing required for social performance (social perception, assessed on the basis of facial expression recognition) and academic performance (cognitive processes, assessed via a general reasoning test) which could contribute to theoretical explanations of the relations that have been empirically identified between social skills deficits and learning disabilities. In Study 1, the subjects were 49 children (average age=8,65 years old), from one public school in the north region of Sao Paulo city. In Study 2, which was a replica of the first, the subjects were 32 children (average age=8,22 years old) from a public school on the outskirts of Cacoal-RO city. The study design was ex-post-facto, associated with the correlational method. The most significant results have shown the mediation function of general reasoning (cognitive processes) in the correlation between social skills and academic performance in children aged equal to eigth and a half years old, or older. The social skills more closely related to general reasoning and facial expression reading were cooperation and responsibility. These results have contributed to the Social Skills Training theory, giving more support to social skills development in infancy for preventing learning disabilities.